Evaluation of Environmental Impact on Ameria Dam in Taiz – Yemen (Thamar University Journal of Natural & Applied Sciences, 2023)
Most 0f construction Dams in Yemen suffered of environmental impact , Ameria dam in Taiz – Yemen, is one of these dams who is suffered of those environmental impact, the results of this research discussed and showing all f types of environmental impacts which influence on the human, animal and international resources. The Maine reason for all of these is pollution of water.